Caveat Jurisconsultus: Warrantless Access to the Client Records of Legal Practitioners - Abraham Hamman; Raymond Koen (Obiter, 2019)
A client legitimately regards almost all communications with his or her lawyer as confidential. However, there are circumstances in which client information is not protected under the attorney-client relationship and is accessible to certain third parties. In South Africa, the client records of legal practitioners are available to the anti-money laundering/combating the financing of terrorism (AML/CFT) agencies, which conduct inspections of law offices under the Financial Intelligence Centre Act 38 of 2001. In terms of a 2008 amendment, these inspections did not require a warrant.In 2014, the South African Constitutional Court declared warrantless non-routine inspections unconstitutional. A legislative amendment of 2017 sought to restore the constitutionality of these inspections. However, neither the Constitutional Court nor the legislature addressed the issue of warrantless routine inspections. For the most part, then, AML/CFT inspections of the premises of legal practitioners need not be warrant-based. The danger here is that client records become ready evidentiary resources for the prosecution service.The Canadian AML/CFT legislation also envisaged a mostly warrantless inspection regime. However, unlike South African legal practitioners, their Canadian counterparts launched a vigorous and sustained assault against the legislative efforts to erode the attorney-client relationship and the legal professional privilege. The Federation of Law Societies of Canada eventually secured exemption for its members from the compliance measures of the AML/CFT legislation. The Canadian experience should serve as an object lesson for the legal profession in South Africa.